Effectiveness of Early Childhood Fine Motor Stimulation Using BubbleWrap at Kindergarten Terang Bangsa 02 Semarang - -, Kristanti Dwi Naomi; -, Edi Waluyo (Universitas Negeri Semarang, 2025)
Many people in Indonesia have a less caring attitude towards environmental cleanliness. Plastic waste is the largest waste produced by Indonesian people. One type of plastic waste is bubble wrap. So this type of plastic is basically usually used for educational needs, especially for early childhood. This research aims to find out whether the use of bubble wrap can stimulate children's fine motor skills at Kindergarten Terang Bangsa 02 Semarang. This research uses a pre-test and post-test experimental design. There were 12 trials in activities to stimulate fine motor skills in early childhood. The population in this study were children aged 4-5 years at Kindergarten Terang Bangsa 02 Semarang with a research sample of 27 students. The results of this study show that there is a level of effectiveness of fine motor stimulation using bubble wrap with the hypothesis H0 being rejected and H1 being accepted. Then the percentage level of the N-Gain score is 58.48%, which means the score is between 0.3 ≤ g ≤ 7 which indicates the category is quite effective. In conclusion, the use of bubble wrap is quite effective in providing stimulation to the fine motor skills of young children at Kindergarten Terang Bangsa 02 Semarang.